Conservation of S20 as an Ineffective and Disposable IFNγ-Inducing Determinant of Plasmodium Sporozoites Indicates Diversion of Cellular Immunity - Hon, Calvin; Friesen, Johannes; Ingmundson, Alyssa; Scheppan, Diana; Hafalla, Julius C. R.; Müller, Katja; Matuschewski, Kai (Frontiers in Microbiology, 2021)
Despite many decades of research to develop a malaria vaccine, only one vaccine candidate has been explored in pivotal phase III clinical trials. This candidate subunit vaccine consists of a portion of a single Plasmodium antigen, circumsporozoite protein (CSP). This antigen was initially identified in the murine malaria model and shown to contain an immunodominant and protective CD8+ T cell epitope specific to the H-2Kd (BALB/c)-restricted genetic background. A high-content screen for CD8+ epitopes in the H2Kb/Db (C57BL/6)-restricted genetic background, identified two distinct dominant epitopes. In this study, we present a characterization of one corresponding antigen, the Plasmodium sporozoite-specific protein S20. Plasmodium berghei S20 knockout sporozoites and liver stages developed normally in vitro and in vivo. This potent infectivity of s20(-) sporozoites permitted comparative analysis of knockout and wild-type parasites in cell-based vaccination. Protective immunity of irradiation-arrested s20(-) sporozoites in single, double and triple immunizations was similar to irradiated unaltered sporozoites in homologous challenge experiments. These findings demonstrate the presence of an immunogenic Plasmodium pre-erythrocytic determinant, which is not essential for eliciting protection. Although S20 is not needed for colonization of the mammalian host and for initiation of a blood infection, it is conserved amongst Plasmodium species. Malarial parasites express conserved, immunogenic proteins that are not required to establish infection but might play potential roles in diverting cellular immune responses.